Analysis Of Cash Management On The Level Of Profitability At Pt Mitrasel The Main Core Makassar - Wildam, Andi Arwinda (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2022)
This research is to analyze the effect of cash management on the profitability of PT. Mitrasel the Main Core Makassar Type of research used in this research is quantitative research with the type of applied research. The type of data used in this research is secondary data, namely in the form of a financial report (expenditure and income, the Cash) PT. Mitrasel the Main Core of Makassar in the period 2018-2020. The results of this study obtained data cash Management significantly influence the profitability ratios ROA on PT Mitrasel the Main Core Makassar by showing the value of sig. (significance) 0,034 < 0,05 (which is the standard value of significance). Then the results of the analysis determinate coefficient (R2), shows the value of R Square 0.750 or based with the provision soft his analysis precentage to 75%. The percentage in dicates that the variable profitability ratios ROA on PT Mitrasel the Main Core Makassar can be explained or influenced by the variable cash management by 75%. While 25% (100%-75%) is influenced by other causes outside of the research variables such as a fundamental factor, which is discipline in activities, intellectual capital owned up to other factors that also may have implications on the level of the ratio of the profitability of a company